JURIDICAL ANALYSIS OF NOVASI IN SETTLING DEBTS OF DEBTORS WHO EXPERIENCE INSOLVENCY IN INDONESIA - Sitompul, Mutiara Andiny (Pena Cendekia Insani, 2026)
Insolvency is a state of the debtor's inability to fulfill its debt payment obligations which is normatively the basis of the bankruptcy mechanism in Indonesia. In the midst of the dominance of settlement through bankruptcy and Suspension of Debt Payment Obligations (PKPU), Indonesian civil law actually provides another alternative through the novation mechanism as stipulated in Article 1413 of the Civil Code. This study aims to analyze the position of novation as a mechanism for settling debts of debtors who experience insolvency and identify juridical obstacles in its application according to positive Indonesian law. This research is normative legal research with a legal and conceptual approach. The results of the study show that novation has legitimacy as a legitimate debt settlement mechanism outside of bankruptcy and PKPU, and can function preventively by removing old debts and replacing them with new engagements so as to prevent debtors from fulfilling the element of